TERAPI PSIKORELIGI DALAM MENINGKATKAN KESEHATAN PASIEN - Hidaayah, Nur (Unusa Press, 2018)
Priority problem of clients who are hospitalized are vulnerable to anxiety and tend to get depressed, so this ailment affects the healing process. Lying weak clients who will feel saturated, thinking negatively about the condition of hers that never improved thus will lower the body's immunity, increases the suffering of the impact a slowdown in the process of adaptation and healing. Psikoreligi therapy is given in the form of guidance on the concept of healthy hospitals from the viewpoint of religion, guidance for dhikr and prayer.Individuals who have spiritual health, life becomes more sincere or resignation towards everything that is given by God, so that will happen the process homeostasis (balance). All protectors are there in the human body working with the obedience of worship, more closer to Allah SWT and clever grateful so created an atmosphere of balance of neurotransmitters in the brain.